2019
DOI: 10.14482/psdc.35.3.155.67
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in college students: values as predictors

Abstract: Miguel Nogueirahttps://orcid.org/0000- 0001-7869-3802 Resumen Los valores básicos de vida se emplean para explicar la satisfacción con la vida; es escasa la investigación que existe centrada en estudiar esta relación con estudiantes universitarios. Por tanto, el presente estudio pretende verificar la predicción de valores de tipo personal, central y social de la satisfacción con la vida de un grupo de 133 estudiantes españoles (108 son mujeres, 81,2 %) con edades comprendidas entre los 18 y los 37 años. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…This effect, according to some research, does not differ according to gender (Yilmaz, 2014). In addition to this, studies such as one carried out with Spanish university students show that life satisfaction depends on the social normative values and moral orientation developed in family environments (Marque et al, 2018).…”
Section: Satisfaction With Life In University Studentsmentioning
confidence: 68%
“…This effect, according to some research, does not differ according to gender (Yilmaz, 2014). In addition to this, studies such as one carried out with Spanish university students show that life satisfaction depends on the social normative values and moral orientation developed in family environments (Marque et al, 2018).…”
Section: Satisfaction With Life In University Studentsmentioning
confidence: 68%
“…One explanation may lie in the fact that life satisfaction may differ according to cultural and contextual values. In this sense, the research conducted by Marques et al [66] found that Spanish students' life satisfaction is largely explained by social criteria. Family and friendship relationships seem to occupy a preeminent place among the factors influencing the life satisfaction of these young people.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the situation of confinement, and the mandatory nature of online teaching, brought with it considerable levels of academic desertion, making higher education institutions propose and demand for themselves greater commitments to guarantee effective education for students [10], integrating both their capacities and needs [11]. It is evident that the impact of all the actions performed by higher education institutions, together with the level of satisfaction of students with respect to the academic processes, will lead to a transformation in education organizations [12].…”
Section: Online Teaching During Emergenciesmentioning
confidence: 99%